The efficacy of gaseous ozone against different forms of Candida albicans - Mahdis Zargaran (Current Medical Mycology, 2017)
Background and Purpose: Ozone is an inorganic molecule with effective antimicrobial properties. Clinical treatment of ozonated water was used for the elimination of Candida albicans, Enterococcus faecalis, endotoxins, and biofilms from root canals. In addition, its therapeutic effects for tinea pedis, ulcers, and leishmaniasis were investigated. The purpose of the present study was to evaluate the fungicidal effects of ozone on different forms of C. albicans. In addition, antifungal susceptibility profile of strains was assessed before and after exposure to ozone. Materials and Methods: Fifty strains of C. albicans were exposed to gaseous ozone at different times. Furthermore, biofilm formation and germ tube production were evaluated when yeast suspensions were exposed to ozone. In addition, antifungal susceptibility of ozone resistant colonies was investiagted as compared to controls. Results: Ozone was highly effective in killing C. albicans in yeast form and inhibition of germ tube formation during 210 and 180 s, respectively. Although with increasing exposure time biofilm production was considerably decreased, resistance to ozone was much higher among vaginal and nail isolates even after 60 min. All the strains were sensitive to fluconazole, caspofungin, and terbinafine pre- and post-ozone exposure. Resistance to amphotericin B was significantly enhanced after exposure to ozone. Conclusion: Although ozone was highly effective on the yeast form of C. albicans and it can inhibit the formation of germ tubes in C. albicans, the complete removal of biofilms did not happen even after 60 min. It seems that ozone therapy induces resistance to amphotericin B.